The practice of a modified bubble CPAP therapy in a rural Sierra Leone SCBU-A pilot study - Qin, Fanghua; Dong, Cuilan; Qiu, Jun; Song, Qingqing; Konomanyi, Kumba; Sesay, Lucinda Sia Fatmata; Xiao, Aiqing (Frontiers in Pediatrics, 2025)
BackgroundContinuous Positive Airway Pressure (CPAP) is an effective intervention for managing neonatal respiratory distress. However, its implementation encounters numerous challenges in resource-limited settings. It is imperative for healthcare professionals to devise highly practical and cost-effective modifications to CPAP systems to address these challenges.ObjectiveTo evaluate the clinical efficacy and operational feasibility of a modified bubble CPAP therapy utilizing locally available materials in reducing respiratory distress and improving survival rates of neonates in the Special Care Baby Unit (SCBU) of the Sierra Leone-China Friendship Hospital.Materials and methods93 neonates with respiratory distress were divided into the control group (n = 48) for nasal cannula oxygen therapy and the observation group (n = 45) for modified bubble CPAP therapy. The modified CPAP device was constructed using locally available materials, such as drinking cups and modified nasal cannulas, with oxygen delivered via concentrators. Respiratory Severity Score, blood oxygen saturation, heart rate, and respiration were monitored with data recorded at admission and 8 h after intervention.ResultsAfter intervention, the neonates in the observation group showed significant improvements in all parameters: decreased RSS scores (7.40 ± 0.986 vs. 5.33 ± 1.447, P < 0.001), heart rate (153.13 ± 5.998 vs. 141.60 ± 8.830, P < 0.001), and respiratory rate (47.87 ± 4.103 vs. 43.47 ± 3.833, P < 0.01), and higher oxygen saturation (73.60% ± 10.636% vs. 91.07% ± 8.940%, P < 0.001) and survival rate (88% vs. 62.5%, P < 0.01).ConclusionThe study indicated that the implementation of modified bubble CPAP therapy enhanced respiratory outcomes and increased survival rates among neonates experiencing respiratory distress in a resource-constrained setting in rural Sierra Leone.